Geological setting of the Chandragiri-Chitlang Range, southwest of Kathmandu Valley, central Nepal (Journal of Nepal Geological Society, 2019)
Geological mapping was carried out in the scale of 1:25000 in the Chandragiri-Chitlang Range of central Nepal, SW of the Kathmandu Valley. In the area, lower four formations of the Phulchoki Group (Paleozoic age) from older to younger sequence, i.e. the Tistung Formation, the Sopyang Formation, the Chandragiri Limestone and the Chitlang Formation along with the Alluvial Fan Deposits and the Kathmandu valley sediments were mapped. Low-grade metamorphic rocks like met sandstone, phyllite, argillaceous limestone, ortho-quartzite and slate dominate the study area. The whole succession of the area is calcareous. The succession consists of a biotitezone in the lower part of the Tistung Formation, whereas the overlying younger succession belongs to a chlorite zone. The Chitlang Formation lies at the core of the Mahabharata Synclinorium and other local-scale structures in the area are the Chitlang Syncline, the Kirtipur Anticline and the Chandragiri Thrust (CT). The repetition of the older Sopyang Formation around the southeastern area and the Tistung Formation around northwestern area over the younger Chandragiri Limestone justifies the presence of the Chandragiri Thrust (CT).